2022
DOI: 10.3390/healthcare10102098
|View full text |Cite
|
Sign up to set email alerts
|

Prospect Theory: A Bibliometric and Systematic Review in the Categories of Psychology in Web of Science

Abstract: Prospect Theory (PT) is an alternative, dynamic explanation of the phenomenon of risky decision making. This research presents an overview of PT’s history in health fields, including advancements, limitations, and bibliometric data. A systematic and bibliometric review of the scientific literature included in the psychological categories of Web of Science (WoS) was performed following the PRISMA 2020 statement for systematic reviews. A total of 37 studies (10 non-empirical and 27 empirical) were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…One of its key ideas is the loss aversion bias, i.e., a greater sensitivity to losses than to potential gains (Liu 2023). Several studies have shown that loss aversion is an important driver of investment decisions (van Dolder and Vandenbroucke 2023;Gisbert-Pérez et al 2022). The behavior of both private investors and financial professionals could be explained by this bias ( van Dolder and Vandenbroucke 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One of its key ideas is the loss aversion bias, i.e., a greater sensitivity to losses than to potential gains (Liu 2023). Several studies have shown that loss aversion is an important driver of investment decisions (van Dolder and Vandenbroucke 2023;Gisbert-Pérez et al 2022). The behavior of both private investors and financial professionals could be explained by this bias ( van Dolder and Vandenbroucke 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing literature, we examine two notable framing devices-i.e., conceptual metaphors [35] and the prospect of gains/losses [36]. Although there is a substantial body of literature on conceptual metaphors for health communication [37][38][39] and an extensive body of work on the framework of gains or losses in health messaging and gambling studies [40][41][42][43][44][45][46][47][48][49], remarkably, there are still few studies that investigate the combined effect of these two types of framing [50].…”
Section: Introductionmentioning
confidence: 99%